Independence, loss, and social identity: Perspectives on driving cessation and dementia. (November 2019) - Sanford, Sarah; Rapoport, Mark J; Tuokko, Holly; Crizzle, Alexander; Hatzifilalithis, Stephanie; Laberge, Sarah; Naglie, Gary; ,
The purpose of this study on driving cessation was to explore the process of coping, decision-making and adaptation through this major life transition. We sought to examine understandings of the emotional responses of drivers and ex-drivers with dementia from the perspective of healthcare providers and family caregivers of persons with dementia. Interviews and focus groups were conducted with several key informant groups: healthcare providers who work with patients with dementia and their families ( N  = 10), representatives from organizations that provide services and support for persons with dementia ( N  = 6), and family caregivers of drivers and former drivers with dementia ( N  = 13). Data analysis involved inductive analytic techniques to generate descriptive and analytic themes from the data. The main themes from the analysis involve the: (1) Loss of independence and disruption to identity connected to emotional responses to driving cessation; (2) Experience of driving cessation as one loss within a series of losses related to dementia; (3) Importance of addressing emotional and identity-related effects in supportive responses to driving cessation; and (4) Support for maintained and adapted roles as a strategy to provide meaning and purpose in the context of driving cessation. Driving cessation can represent a significant disruption to identity, and is closely linked to losses, such as independence, within people's broader experiences of grief and loss associated with dementia. The findings suggest the need for supportive responses that address unique emotion and identity-related aspects of driving cessation for people with dementia and their family caregivers.